O professor de língua inglesa no audiolingual: uma abordagem sociointeracionista acerca dos textos sobre o trabalho docente. - Santos, Fernando Antonio Fragoso dos (2011)
Our dissertation is included in the Aplied Linguistics and Social Practices Context part of the Post-graduation Program in Linguistics at Universidade Federal da Paraíba, focusing on the representations on teachers actions in work situations. We work with the teaching of the English language performed in a language school located in Joao Pessoa-PB, whose methodology is based on the Audiolingual Method. We believe that if such method prescribes the teacher s actions, it is also a way to make this teacher reflect about his/her practice highlighting points of views and changes. Our theoretical perspective shares the studies developed by the Socio and Discursive Interactionism (SDI) approach whose main reference is Bronckart (1997 e ss.) and the other researchers. Our focus is to identify and analyze the relation between language and educational work in texts produced before and after the work situation. Behind such perspective, we present our main goal that is to understand the way such texts reflect representations, interpretations and social evaluations concerning the teacher s activity. We used the action categories developed by Bronckart and Machado (2004) and Bulea (2010) to analyze the texts before and after the teacher s work. In a first moment, we identified such categories in a prescriptive document previously implicated in the classroom context, considering the roles attributed to the teachers. After that, we verified the actions mobilized by the teachers throughout their interviews and the roles they assign themselves. We believe that this research represents a relevant contribution to reflect about the way prescriptive documents really influence the teaching practice and the way teachers usually deal with such prescriptions.